Developing an instrument to measure student's perception of the medical education curriculum from the perspective of Communities of Practice theory - Yoga Pamungkas Susani; Gandes Retno Rahayu; Yayi Suryo Prabandari; Rossi Sanusi; Harsono Mardiwiyoto (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2020)
The concept of participation as a learning process is essential to foster professional identity development. Faculties are expected to provide a curriculum that supports students' participation in the profession's context. Curriculum evaluation is needed to assess the extent to which curriculum implementation supports participation. In this regard, this study aims to develop instruments that measure students' perceptions of the medical education curriculum. The blueprint for the instrument's development was based on the concept of participation in communities of practice theory. Qualitative research, which involved 17 pre-clinical and clinical medical students as participants, was conducted to explore medical students' perception about formal learning activities that encourage participation. The results were used to generate the items. A series of review processes, item reduction, revisions, and analysis generated 20 items in four factors, namely: engagement support, imagination support, convergence, and feedback. This shows that the instrument is multidimensional. The instrument also has good discriminant validity and composite reliability.